2010
DOI: 10.1109/tps.2010.2042457
|View full text |Cite
|
Sign up to set email alerts
|

$X$-Pinch Experiments on 1-MA “QiangGuang-1” Facility

Abstract: The results of an experimental investigation of X -pinch performance on the 1-MA "QiangGuang-1" facility are presented. "QiangGuang-1" is a linear-transformer-driver-based low-impedance pulsed power machine which provides a peak current of 0.9-1.3 MA and a 10%-90% rise time of 50-60 ns. X -pinch loads with 2-32 wires of different wire materials (Al, W, and Mo) with wire diameters from 25 to 100 μm have been tested. The number and size of bright spots, timing of the first X-ray burst, X -pinch dynamics, and X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The final results are shown in figure 3(b-d) showing the dynamics of the Mo wire X-pinch. It is indicated that the sizes of x-ray sources are about 1-2 mm which are roughly in agreement with other results [10,11]. Due to different view angles which are relative to the wire arrays, the x-ray source patterns are different, indicating the three-dimensional information of the x-ray source generated by X-pinch is complex.…”
Section: Jinst 17 P09030supporting
confidence: 88%
“…The final results are shown in figure 3(b-d) showing the dynamics of the Mo wire X-pinch. It is indicated that the sizes of x-ray sources are about 1-2 mm which are roughly in agreement with other results [10,11]. Due to different view angles which are relative to the wire arrays, the x-ray source patterns are different, indicating the three-dimensional information of the x-ray source generated by X-pinch is complex.…”
Section: Jinst 17 P09030supporting
confidence: 88%
“…The experiments were conducted on the "Qiangguang I" facility, which is a linear-transformer-driver-based pulsed power generator located at the Northwest Institute of Nuclear Technology, 20 with the peak current and rise time (10%-90% peak current) $1.3 MA and $90 ns, respectively, for a typical wire-array Z-pinch implosion. The main side-on diagnostic instruments included two soft x-ray power meters, which have an almost flat spectral response to photon energies from 50 eV to 1250 eV, to measure the radial radiation powers, an optical streak camera to diagnose the boundary of the tungsten plasma, and a four-frame ultraviolet (UV) laser shadowgraph at a wavelength of 265 nm.…”
Section: Resultsmentioning
confidence: 99%
“…20 QiangGuang-1 facility is a pulsed power machine composed by a linear-transformerdriver (LTD) in series with several low impedance waterdielectric transmission lines. During the experiments, it provided a peak load current of $1 MA and 10%-90% current rise time of 50-60 ns.…”
Section: A Experimental Setupsmentioning
confidence: 99%